PATTERNS OF RISK AND RESILIENCE IN AFRICAN AMERICAN AND LATINO YOUTH. Issue 8 (November 2015) - Ernestus, Stephanie M.; Prelow, Hazel M.
<x xml:space="preserve">Abstract</x> The present study identified subgroups of adolescents with distinctive patterns of risk and protective factors in early adolescence and examined the psychosocial adjustment of these subgroups in middle to late adolescence. A total of 930 low‐income African American and Latino adolescents were surveyed as a part of the Welfare, Children & Families: A Three City Study. Three clusters of risk and protective variables were identified at 10–14 years of age; one cluster was high on protective factors, one high on risk factors, and another mixed with protective factors and high community risk. Six years later, variable‐centered analyses demonstrated differences in delinquency, psychological distress, peer and romantic relationships, and sexual history between clusters. Individuals in the resilient and mixed clusters were the most similar overall, and demonstrated significantly more positive outcomes than their risk‐cluster peers. Findings illustrate how the integration of person‐ and variable‐focused approaches provides more information about the developmental outcomes of youth in investigations of resilience.